ANALISA LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA INDUSTRI PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Ajie Rahman; Oktarini Khamilah; Rahima Boru Purba (Ensiklopedia Education Review, 2021)
This study is aimed at analyzing cash flow statements to assess the financial performance of companies engaged in mining in 2016-2020. This type of research is descriptive quantitative research, the data used is secondary data, namely the cash flow statements of mining companies totaling 10 companies listed on the Indonesia Stock Exchange (IDX). The analytical technique. The method used is using the cash flow ratio by comparing each cash flow statement from each company engaged in the mining sector each year. Based on the cash flow ratio, it is concluded that the majority of mining companies have not have good performance. Of the five ratios, only the Cash Coverage Ratio is the most much can be achieved by mining companies. There are 6 (six) a company that has a good cash coverage ratio value ( 1), namely PT.Bukit Asam Tbk, PT. Mitra Investindo Tbk, PT. Timah Tbk, PT. Golden Eagle Energy Tbk, PT. Citatah Tbk, PT. Central Omega Resources Tbk. These six companies are considered have the ability of the company's operating cash flow to cover interest expenses company. Meanwhile, the value of the Fund Flow Coverage Ratio and the Total Debt Ratio which were in good criteria for 3 (three) consecutive years was only achieved by PT Bukit Asam Tbk. Likewise with the other five ratios, only two companies are consistent has a value above the standard during the three-year observation period, and only PT Bukit Asam Tbk consistently has a ratio above the standard of 7 (seven) current ratios cashKeywords: Statement of Cash Flows and Financial Performance.